Abordagens de ensino e experiência de aprendizagem: uma pesquisa narrativa a partir do site BBC Learning English - Morotti, Rafael Antonio (2022)
We usually search for free online contents in order to learn foreign languages, as well as we recommend it to other people. In this sense, the BBC Learning English webpage is a reference for teachers and learners. Although English learners from all over the world have been attended this website, there are few studies on its contents, especially regarding its teaching approaches. Considering this fact, the general objective in this study is to investigate the possible language teaching approaches underlying the contents of the website. For this purpose, this research was grounded on authors who have produced relevant works in this area, such as Anthony (1963), Richards and Rodgers (1986), Almeida Filho (1993, 1997, 2000), Larsen-Freeman (2003, 2011), Littlewood (1981) and Lewis (1993, 2000, 2008). As a methodology, one developed a narrative research from the writing of a study diary, based on Bailey (1991), Barcelos (2020), Barkhuizen (2015), Pavlenko (2007), among others. The comparison between the characteristics of approaches and the diary reports generated relevant data on how the page promotes the teaching of English.